Evidence-based practice among a group of Malaysian dental practitioners. - Yusof, Z.Y.M.; Han, L.J.; San, P.P.; Ramli, A.S. (American Dental Education Association, 2008)
The objective of this study was to assess dentists' knowledge and use of evidence-based practice (EBP), including their attitudes toward and perceptions of barriers that limit the use of EBP. A cross-sectional survey was used with self-administered questionnaires involving dental practitioners in the state of Selangor, Malaysia. One hundred ninety-three replies were returned, for a response rate of 50.3 percent. More than two-thirds (135/193, 69.9 percent) of the respondents had heard of EBP. Out of the 135 respondents who had heard of EBP, a majority agreed it was a decision-making process based on evidence (127/135, 94.2 percent) and involved a series of steps from formulating the research question, locating and assessing the evidence, to applying it if suitable (129/135, 95.6 percent). Out of the 135 respondents who had heard of EBP, a high percentage agreed that EBP improved their knowledge and skills (132/135, 97.8 percent) and treatment quality (132/135, 97.8 percent). For advice, a majority of the 135 respondents frequently consulted friends and colleagues (123/135, 91.1 percent), made referrals (120/135, 88.9 percent), consulted textbooks (112/135, 83.0 percent), and referred to electronic databases (90/135, 66.7 percent). Out of the 135 respondents, many perceived EBP as very important (59/135, 43.7 percent) and important (58/135, 43.0 percent) and were interested to learn further information about EBP (132/135, 97.8 percent). The main reported barriers were lack of time (87/135, 64.4 percent), financial constraints (54/135, 40.0 percent), and lack of knowledge (38/135, 28.1 percent). A majority of the 135 respondents had knowledge of and positive attitudes towards EBP. However, due to barriers, a majority of them preferred colleagues, textbooks, and referrals for advice instead of seeking evidence from electronic databases.